The Relationship Of Nurse’s Caring Behavior With Level Of Patient Satisfaction In The Inpatient Room: Literature Review - Andan Firmansyah; Heni Marliany; Sani Dayanti (Jurnal Vocational Nursing Sciences (VNUS), 2020)
Nurse care behavior is one of the important aspects in fulfilling patient satisfaction, care covers human relationships that are one of the quality indicators of home service It hurts. No. rarely conflict between nurses and patients as a result of the lack of care given to patients so that disappointment and discontent and low trust Patient. Level. Satisfaction is a function of the difference between performance felt with hope. The aim of this literature review is to identify and describe research that investigates the relationship between caregiver behavior and patient satisfaction in the living room. The method used in writing this article is literature review with searches sourced from an electronic data base including Google Scholar, DOAJ, and Garuda portal with the keywords nurse caring behavior and patient satisfaction. Researchers only selected articles published in the period 2015-2020 with 15 related journals. The data obtained were analyzed, arranged systematically, compared with each other and discussed related literature. The results of the literature review showed that there was a relationship between nurses' caring behavior and the level of patient satisfaction in the inpatient room.